The Effect of The Marketing Mix on Purchase Decisions at Sate Putra Condong - Muhammad Rifyal Fadilah (PT. Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of the marketing mix on consumer purchase decisions at Sate Putra Condong, an MSME. The marketing mix examined in this study comprises four elements: product, price, place, and promotion. The study employed a quantitative approach with an associative research design. Primary data were collected through questionnaires distributed to 96 consumers of Sate Putra Condong selected using purposive sampling. The sample size was determined using the Lemeshow formula because the population size was unknown. The data were analyzed using descriptive analysis, classical assumption tests, simple linear regression analysis, hypothesis testing, and the coefficient of determination with the assistance of SPSS software. The descriptive results indicate that the implementation of the marketing mix was rated very good, while consumer purchase decisions were rated good. The hypothesis test results demonstrate that the marketing mix has a positive and significant effect on consumer purchase decisions. The coefficient of determination indicates that the marketing mix explains 83.9% of the variation in purchase decisions, while the remaining 16.1% is influenced by factors outside the research model. These findings indicate that the integrated management of product, price, place, and promotion can strengthen consumer purchase decisions at Sate Putra Condong